Analysis of calculation of fresh-air demand for road tunnel ventilation design in China. (September 2020) - Wang, Xu; Wang, Mingnian; Chen, Jia; Yan, Tao; Bao, Yifan; Chen, Jinyu; Qin, Pengcheng; Li, Kunjie; Deng, Tao; Yan, Guanfeng
Highlights: We investigated the similarities and differences between three tunnel ventilation design standards. Emission generation rate formula, base emission rates and time factors were compared. Calculation example show 24.5% and 21.7% difference in fresh-air demand between three standards. The results will provide meaningful economic reference for road tunnel ventilation design in China. Abstract: At present, road tunnel ventilation system design in China is calculated with reference to the 2014 China Guidelines. However, with the continuous renewal of vehicle and more stringent emission laws, calculation results based on parameters in the 2014 China Guidelines are significantly different from the actual situation, which will cause a great waste of ventilation system. According to investigating the domestic and foreign tunnel ventilation design standards, a calculation example was used to analysis the impact of emission generation formula, base emission rates and time factors on ventilation system design. The results show that 2017 Shanghai Code and 2019 PIARC Ventilation Report consider the impact of NO2 and non-emission particles on fresh-air demand in tunnel, while 2014 China Guidelines do not. For base emission rates, three standards take 2000, 2010 and 2018 respectively as the base years. The 2014 China Guidelines provides the base emission rates in a fixed value, while the other two criteria provide more precise values. For time factor, three standards stipulate the annual average attenuation is 2%, 6% and 5% respectively. Compared with 2014 China Guidelines, the required fresh-air flow rate of an example tunnel calculated by the 2017 Shanghai Code and 2019 PIARC Ventilation Report was reduced by 24.5% and 21.7% respectively. The research results clarify the similarities and differences between three road tunnel ventilation design standards, and quantitatively present the gaps in calculation of fresh-air demand caused by different factors, which provide a reference for the ventilation design of tunnel in China.